Mangosteen Peel Liquid-Protected Soybean Meal Can Shift Rumen Microbiome and Rumen Fermentation End-Products in Lactating Crossbred Holstein Friesian Cows - Phesatcha, Kampanat; Phesatcha, Burarat; Wanapat, Metha (Frontiers in Veterinary Science, 2022)
Rumen bypass protein can enhance protein availability in the lower gut. This study investigated the use of liquid-containing phytonutrients in dairy cows as a dietary additives to reduce rumen protein degradation. Four crossbred lactating Holstein Friesian cows (75% Holstein Friesian with 25% Thai native breed) with an initial body weight (BW) of 410 ± 20 kg were randomly assigned to a 2 × 2 factorial arrangement [two crude protein (CP) levels with soybean meal (SBM) or mangosteen peel liquid-protected soybean meal (MPLP)-SBM] in a 4 × 4 Latin square design experiment. Dietary treatments were as follows: T1 = SBM in low crude protein concentrate (LPC) (SBM-LPC); T2 = MPLP-SBM in LPC (MPLP-SBM-LPC); T3 = SBM in high crude protein concentrate (HPC) (SBM-HPC); T4 = MPLP-SBM in HPC (MPLP-SBM-HPC). Apparent digestibilities of organic matter (OM) and neutral detergent fiber (aNDF) were increased (p < 0.05) by CP level in the HPC diet (19% CP), with higher OM and aNDF digestibilities. High crude protein concentrate increased (p < 0.05) the propionic acid in the rumen but reduced (p < 0.05) the acetic acid-to-propionic acid ratio and methane (CH4) production. Rumen microbial populations of the total bacteria, Fibrobacter succinogenes and Butyrivibrio fibrisolvens were increased (p < 0.05) by HPC. Real-time PCR revealed a 30.6% reduction of rumen methanogens by the MPLP-SBM in HPC. Furthermore, efficiency of microbial nitrogen synthesis (EMNS) was 15.8% increased (p < 0.05) by the MPLP-SBM in HPC when compared to SBM-LPC. Milk yield and milk composition protein content were enhanced (p < 0.05) by both the CP level in concentrate and by MPLP inclusion. In this experiment, a high level of CP and the MPLP-SBM enhanced the ruminal propionate, shifted rumen microbiome, and enhanced milk yield and compositions.